β-hydroxybutyrate suppresses pathological changes of blood-induced arthropathy in rats - Ryohei Kawasaki; Asuka Sakata; Kohei Tatsumi; Seiji Mitani; Maiko Takeda; Shogo Kasuda; Naoki Matsumoto; Suguru Harada; Tetsuhiro Soeda; Yukiko Nishida; Yasushi Yoshimura; Midori Shima (Scientific Reports)
Abstract Arthropathy is a common complication in haemophilia and decreases quality of life. It has been known that concentrations of β-hydroxybutyrate (BHB) in blood are increased by a ketogenic diet, and elevated levels of circulating BHB restricts the progression of inflammation-mediated joint pathological changes. We hypothesized that elevation of blood BHB concentrations could be effective for reducing the progression of bleeding-induced arthropathy by moderating the inflammatory responses of macrophages. In this study, we investigated whether BHB alleviates the arthropathy caused by repeated intra-articular blood injection in rats. To increase blood BHB levels, rats were fed with ketogenic diet. Repeated intra-articular blood injection induced significant joint swelling, whereas ketogenic diet intake significantly increased blood BHB concentrations and ameliorated the joint swelling. The periarticular tissue-fibrosis observed in the control diet intake group appeared to be significantly alleviated in the ketogenic diet intake group. In addition, the IL-1β, which is involved in the progression of arthropathy, levels in the supernatants of blood-exposed macrophages derived from THP-1 cell line were significantly suppressed by BHB supplementation. In summary, BHB moderated the pathological joint changes caused by intra-articular blood exposure.